Modelling the filling process of lithium‐ion batteries. Issue 1 (15th March 2018) - Neumann, Tim; Boettcher, Konrad; Ehrhard, Peter
Abstract: Lithium‐ion batteries are composed of several single cells, each consisting of conductive, impermeable electrodes made of aluminum and copper. Both are coated with a thin, porous layer on both sides (collectors) and a thin, non‐conductive and permeable layer is separating them. As the layers are stacked, the liquid enters the battery at all front edges, while the gas is trapped inside. To estimate the filling process of these batteries with the viscous suspensions containing the electrolyte, a model for the flow of a well‐wetting liquid displacing a gas in a single cell is established. This can be modeled as a stack of three porous layers with heterogeneous characteristics (cf. figure 2). The porous structure of the electrode coatings is approximated as a packed bed of spheres. Considering the small ratio of layer thickness to particle diameter, the influence of the wall effect onto the relevant forces has to be taken into account. These models according to the hydrodynamics of this multi‐phase flow are implemented into the commercial CFD‐software Ansys CFX. Derived from the numerical results, a 1D description is developed to specify the whole filling process. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)